The struggle to define a nation: rethinking religious nationalism in the contemporary Islamic world - Demichelis, Marco; Maggiolini, Paolo (The modern Muslim world, 2017)
Frontmatter -- TABLE OF CONTENTS -- ABOUT THE CONTRIBUTORS -- INTRODUCTION. THE STRUGGLE TO DEFINE A NATION: RETHINKING RELIGIOUS NATIONALISM IN THE CONTEMPORARY ISLAMIC WORLD / Demichelis, Marco / Maggiolini, Paolo -- 1. RELIGIOUS NATIONALISM IN THE OFFICIAL CULTURE OF MULTI-CONFESSIONAL LEBANON / Henley, Alexander D. M. -- 2. SYRIA’S LEBANONIZATION: AN HISTORICAL EXCURSUS WITHIN THE ‘NON-EXISTENCE’ OF SYRIAN NATIONAL IDENTITY / Demichelis, Marco -- 3. NATION-NARRATING MONARCHIES: THE RELIGIOUS ‘SOFT POWER’ OF THE MOROCCAN AND JORDAN KINGS / Preuschaft, Menno -- 4. SAUDI NATIONAL IDENTITY: HISTORICAL AND IDEATIONAL DIMENSIONS / Maestri, Elena -- 5. RELIGION AND NATIONALISM: PALESTINIAN CHRISTIANS AND RELIGIOUS LEADERSHIP IN THE MIDST OF THE ISRAELI-PALESTINIAN CONFLICT / Maggiolini, Paolo -- 6. ‘UNDER THE SAME FLAG’: THE COPTS OF EGYPT AND THE CHALLENGES OF NASSERIST NATIONALISM / Melcangi, Alessia -- 7. THE LONER DESPERADO: OPPRESSION, NATIONALISM AND ISLAM IN OCCUPIED PALESTINE / Pappe, Ilan -- 8. SELF-SACRIFICE AND FORGIVENESS: RELIGION AND NATIONALISM IN THE NEW ISRAELI AND PALESTINIAN CINEMA / Morad, Yael Ben-Zvi -- 9. RELIGION AND NATION BUILDING IN TURKEY: THE ROLE OF INSTITUTIONALIZED RELIGION IN THE CASE OF DIYANET / Şen, Gül -- 10. JUNDALLAH AND RADICAL RELIGIOUS NATIONALISM / Shayan, Fatemeh -- 11. NATIONALISM AND ISLAMISM AS OPPOSING DETERMINANTS OF IRANIAN NATIONAL IDENTITY / Saleh, Alam -- 12. EVOLVING FACE OF PAKISTAN’S RELIGIOUS NATIONALISM / Ali Saleem, Raja Muhammad -- 13. THE LIMITS OF SECULAR NATIONALISM: REVISITING THE POLITICS OF ISLAM AND NATIONAL IDENTITY IN BANGLADESH / Kabir, Humayun -- 14. THE BROKEN MIRROR: HOW THE CONTEMPORARY JIHADIST NARRATIVE IS RE-SHAPING THE CLASSICAL DOCTRINE OF JIHAD / Redaelli, Riccardo -- 15. EMERGING TRENDS IN THE BROADER JIHADI GALAXY: BETWEEN RADICALIZATION AND NEW MODELS OF JIHADISM / Plebani, Andrea -- 16. CONCLUSION 1: FROM THE NAHDA TO NOWHERE? / Branca, Paolo -- 17. CONCLUSION 2: DEMOCRACY, NATIONALISM AND RELIGION IN THE ARAB WORLD / Choueiri, Youssef M.